2011
DOI: 10.1111/j.1551-2916.2011.04568.x
|View full text |Cite
|
Sign up to set email alerts
|

Strong Upconversion Photoluminescence and Large Ferroelectric Polarization in Er3+–Yb3+–W6+ Triply Substituted Bismuth Titanate Thin Films Prepared by Chemical Solution Deposition

Abstract: Strong upconversion photoluminescence and large ferroelectric polarization were observed for the first time in layered structure Er3+–Yb3+–W6+ triply substituted bismuth titanate thin films. The thin films were prepared on fused silica and Pt(111)/Ti/SiO2/Si substrates by chemical solution deposition. Two green emission bands and a red one were observed in the upconversion photoluminescence spectra for all the films pumped by a 980 nm laser diode, which correspond to 2H11/2, 4S3/2, and 4F9/2 to 4I15/2 transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Activator Ni 2+ seems to show little effect on the ferroelectric property, which is similar to earlier reports by other researchers studying metal-ion doped ferroelectrics. 20,21 Fig. 1 NIR PL spectra of Ni 2+ -doped BST samples under 360 nm excitation are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activator Ni 2+ seems to show little effect on the ferroelectric property, which is similar to earlier reports by other researchers studying metal-ion doped ferroelectrics. 20,21 Fig. 1 NIR PL spectra of Ni 2+ -doped BST samples under 360 nm excitation are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that chemical substitution is capable of tuning crystal structure and symmetry in perovskite oxides and therefore dramatically altering the materials' properties. In fact, REdoped ferroelectric oxides possessing perovskite structure have been studied by Bao et al 20,21 The simultaneous existence of ferroelectric and optical properties was observed, which may be attractive for applications in multifunctional devices. Our recent works indicate that tunable and enhanced upconversion luminescence can be realized in RE-doped ferroelectric BaTiO 3 (BTO) materials resulting from the benet of the unique crystal structure of ferroelectric perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…During the fabrication of Bi 3.46 Ho 0.04 Yb 0.5 Ti 3 O 12 : xLi phosphors, LiNO 3 (99%, Macklin, Shanghai, China), Bi(NO 3 ) 3 •5H 2 O (99%, SCRC, Shanghai, China), Ho(NO 3 ) 3 •6H 2 O (99.99%, Rknerc, Shanghai, China), Yb(NO 3 ) 3 •5H 2 O (99.99%, Rknerc, Shanghai, China) and Ti(OC 4 H 9 ) 4 (AR, Macklin, Shanghai, China) were used as the precursors of Li, Bi, Ho, Yb, and Ti ions, respectively. Ho, Yb, and Ti precursors were weighed according to stoichiometry of the formula of Bi 3.46 Ho 0.04 Yb 0.5 Ti 3 O 12 : xLi, and Bi and Li precursors exceeded 15% and 10% to supplement Bi and Li loss because both of them can partly volatilize during high-temperature treatment [20]. At first, the weighted Li, Bi, Ho, Yb precursors were put into a beaker, and then 15 mL acetic acid (AR, Macklin, Shanghai, China) was added rapidly, followed by heated under 55 • C and stirred for 15 min, and then cooled down to room temperature to obtain solution denoted as A liquid.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that the host material plays an important role in the up‐conversion process in Er 3+ ions. Up to now many kinds of host materials have been investigated, for example, glasses, polycrystalline powders, single crystals, thin films, nano‐crystals, and transparent ceramics . However, the application is still restricted because of poor chemical stability and the low laser‐induced damage threshold of hosts …”
Section: Introductionmentioning
confidence: 99%
“…Up to now many kinds of host materials have been investigated, for example, glasses, polycrystalline powders, single crystals, thin films, nano-crys-tals, and transparent ceramics. [14][15][16][17][18][19][20] However, the application is still restricted because of poor chemical stability and the low laser-induced damage threshold of hosts. 21 Besides the excellent electrical properties, PMN-PTs are the most promising nonlinear optical materials because of the extremely high electro-optic (EO) coefficient and the strong photorefractive effect.…”
Section: Introductionmentioning
confidence: 99%